Yakym Yarema’s philosophical and pedagogical ideas in discursive practices of education - Honcharenko, Olha (Kultura-Społeczeństwo-Edukacja, 2019)
In this paper on the basis of comparative analysis the similarity of Yakym Yarema’s and Kazimierz Twardowski’s main philosophical and pedagogical ideas has been identified. The analysis of these ideas proves that Ukrainian scientist represents Twardowski’s educational practices as well as reflects the traditions of Vienna philosophical school by Franz Brentano which history goes back to Aristotle’s philosophy. The value of Yakym Yarema’s philosophical and pedagogical ideas in the present educational discourse has been shown in the article.